Media Promosi Digital pada Produk UMKM Kue dan Ikan Kering di Kecamatan Sungai Beremas - Alya, Ilhami; Annas, Firdaus; Santika, Mira; Yanti, Rahma (Yayasan Lembaga Studi Makwa, 2025)
This research aims to increase the sales of cake and dried fish products in Micro, Small, and Medium Enterprises (MSMEs) in Sel Beremas District through the development of an OpenCart-based e-commerce platform. The research is motivated by the limited access to online markets and the lack of digital knowledge among MSMEs. The research method used is Research and Development (R&D) with a user-oriented approach. The initial stage involved data collection through surveys and interviews to identify the needs of MSMEs and consumer preferences. The results of the data analysis were used as a basis for designing a user-friendly and attractive platform. The key features developed include an interactive product catalog, diverse payment systems, integration with social media, and order tracking features. The developed e-commerce platform was then implemented and evaluated. The evaluation results showed a significant increase in several performance indicators, such as website traffic, transaction value, and customer satisfaction. Additionally, the platform successfully enhanced the brand awareness of MSMEs in the online market. This study concludes that the development of the OpenCart-based e-commerce platform is an effective solution to increase MSME product sales in Sel Beremas District. This platform not only expands market reach but also provides convenience for consumers in making transactions. It is hoped that this research can serve as a reference for the development of other MSMEs in utilizing digital technology to enhance business competitiveness.